PENINGKATAN PROMOSI KESEHATAN DALAM UPAYA PENCEGAHAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS IV KOTO KINALI KABUPATEN PASAMAN BARAT - Putri Nilam Sari; Devhani Fitri; Desri Resfita; Irene Sandra Olivia; Mivtahurrahimah Mivtahurrahimah; Nadia Nadia; Orina Vandini; Ulya Azizi Sukma; Zilhasrati Zilhasrati (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Indonesia has experienced a shift in disease patterns from highly infectious diseases to non-communicable diseases, one of which is hypertension. Complications of hypertension can harm the body, so it is necessary to increase public understanding to prevent further hypertension impacts. The achievement of hypertension health services at Puskesmas IV Koto Kinali was 20.96% of the set target, meaning that 79.04% of hypertensive patients had not received regular treatment. So that efforts to improve health promotion in preventing hypertension in the work area of hospital IV Koto Kinali, West Pasaman Regency, need to be carried out. This activity aims to make efforts to solve problems so that hypertension sufferers take regular treatment in the work area of the hospital IV Koto Kinali. Methods of activities included counseling about hypertension, giving leaflets, hypertension exercise, and sticking hypertension posters. Evaluation of the knowledge of the counseling participants showed that there was an increase in public knowledge and awareness about the dangers of hypertension and its prevention. The results of activities from counseling about hypertension are considered as one of the effective ways to improve health promotion in preventing hypertension in hospital. This activity concludes that the provision of health promotion related to hypertension with PowerPoint media runs smoothly. Visitors who listen are enthusiastic about the provision of material by the group. It is hoped that this promotional activity can continue to be carried out and regularly scheduled at hospital IV Koto Kinali and extension facilities such as places and teaching aids can be continuously provided and updated.